Pengaruh Profitabilitas, Leverage dan Likuiditas Terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Makan dan Minuman yang Terdaftar di BEI 2021-2023 - Riski Kurniawan; Emilia Gustini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The aim of this research is to obtain empirical evidence and analyze the influence of profitability, leverage and liquidity on company value. Type The research used is a quantitative approach. The population of this study is a Food and Beverage Sub Sector Company that listed on the Indonesian Stock Exchange for the 2021-2023 period. Sampling technique used purposive sampling technique to obtain 90 reports financial results obtained from a sample of 30 companies over a three year period. Hypothesis testing was carried out using multiple regression analysis using SPSS version 26 with a significance value set at 5%. The results of this research show that the variables are profitability, leverage and liquidity has a significant effect on company value.